Chemistry simulations - Pelangi Multimedia Technologies Sdn. Bhd.; Penerbitan Pelangi Sdn. Bhd. (Selangor : Pelangi Multimedia Technologies Sdn. Bhd. : Penerbitan Pelangi Sdn. Bhd. (distributor), 2006)
This cd-rom provides parameters of an experiment that can be set and its results can be shown in real time. All simulations are calculated based on scientific formula to ensure that the results are accurate
PTSL : volume 1 ; volume 2
System requirements : Windows 98/Me/2000/XP
Keywords: Chemistry -- Study and teaching -- Simulation methods; Chemistry -- Study and teaching (Secondary); Chemistry